Islamic Religious Education Learning Innovation Based on Student Centered Learning: A Study on Learning Fiqh Nisa' - Hidayah, Nurul; Romelah, Romelah; Hikmatulloh, Hikmatulloh (Fitrah: Journal of Islamic Education, 2024)
The challenges of globalization and modernization can blur students' Islamic identity, especially in learning fiqh nisa', due to the influence of outside cultures that are often contrary to Islamic values. Therefore, learning innovations are needed that encourage active student involvement and provide direct experience from the reality of everyday life. Among the forms of learning innovation is combining Student Centered Learning (SCL) and Experiential Learning (EL) in learning fiqh nisa'. This research analyzes the innovation with a focus on the form, contribution, and constraints of innovation. This research was conducted at the Personality and Leadership Development Program of Muhammadiyah University of Malang. The research method used is qualitative, with a phenomenological study approach. The results revealed that the forms of learning innovations implemented were problem-based learning and social experience projects. This innovation contributes to increasing student involvement, linking material with real life, and developing critical thinking. The obstacles are the lack of teaching skills, limited resources, resistance to change, time constraints, and the challenge of connecting Islamic values with modern reality. The research findings support Imam al-Ghazali's theory of at-Talim min Khilal al-Khibra wa at-Tatbiq, which prioritizes learning through experience and application.